Revision of the orb-weaving spider genus Verrucosa McCook, 1888 (Araneae, Araneidae) - Lise, Arno A.; Kesster, Cynara C.; Da Silva, Estevam L. Cruz (Zootaxa, 2015)
The araneid spider genus Verrucosa McCook, 1888 is revised. Five of the seven previously known species, V. arenata (Walckenaer, 1841), V. lampra Soares & Camargo, 1948, V. meridionalis (Keyserling, 1892), V. undecimvariolata (O. Pickard-Cambridge, 1889) and V. zebra (Keyserling, 1892), are redescribed and illustrated. In addition, 37 new species of Verrucosa from the Neotropical region are described and illustrated: V. cachimbo n. sp., V. tarapoa n. sp., V. scapofracta n. sp., V. carara n. sp., V. latigastra n. sp., V. guatopo n. sp., V. cuyuni n. sp., V. benavidesae n. sp., V. rancho n. sp., V. excavata n. sp., V. meta n. sp., V. levii n. sp., V. chanchamayo n. sp., V. manauara n. sp., V. brachiscapa n. sp., V. macarena n. sp., V. pedrera n. sp., V. lata n. sp., V. galianoae n. sp., V. suaita n. sp., V. coroico n. sp., V. florezi n. sp., V. hoferi n. sp., V. caninde n. sp., V. opon n. sp., V. silvae n. sp., V. avilesae n. sp., V. tuberculata n. sp., V. alvarengai n. sp., V. apuela n. sp., V. bartica n. sp., V. cajamarca n. sp., V. canje n. sp., V. cuyabenoensis n. sp., V. sergipana n. sp., V. simla n. sp. and V. rhea n. sp. Mahadiva reticulata O. P.-Cambridge, 1889 is removed from the synonymy of Verrucosa arenata (Walckenaer, 1841) and is recognized as a valid species, Verrucosa reticulata. Araneus cylicophorus Badcock, 1932 is transferred to Verrucosa by Mello-Leitão (1946) removed from the synonymy of Verrucosa meridionalis (Keyserling, 1892) and recognized as a valid species. The male of Verrucosa meridionalis (Keyserling, 1892) is described for the first time. Distributional maps are provided for all species.